Significance of HBsAg Expression in Placental Tissue with Serum Positivity in Hepatitis B Virus-infected Mother - Kalatiku, Jane Magdalena; J Nelwan, Berti; Zainuddin, Andi Alfian; Kaelan, Cahyono; Achmad, Djumadi; Masadah, Rina (Faculty of Medicine, Hasanuddin University., 2023)
Introduction: Hepatitis B virus infection in fetal and newborn may result from the intrauterine vertical transmission. The purpose of our study is to determine the association between HBsAg expression in the placental and HBsAg serum in pregnant women. Methods: Total 67 placental tissues and serum were obtained from HBV-infected mothers. This study was conducted in various hospitals in Makassar, Indonesia from December 2017 until August 2018. Maternal serum and placental tissues were tested by ELISA and Immunohistochemistry staining. Results: 67 samples from placental tissues and serum were categorized into two different levels of serum titer and staining positivity. Twenty nine samples (43.3%) were categorized in low titer of HBsAg positive serum and 38 samples (56.7%) in high titer of HBsAg positive serum. From the total of 67 placental samples, 43 (64.2%) samples had positive expression of HBsAg immunohistochemistry staining and 24 (34.8%) samples had negative expressions. Conclusions: There was a significant correlation between the expressions of HBsAg in the placental tissues and serum titers of HBV-infected mothers that is important in predicting the risk of transplacental transmission. The results of this study can be used as guidelines for the prevention and therapeutic approach of mother-to-child HBV infection.